Illustrative Tutorials for ProThermDB: Thermodynamic Database for Proteins and Mutants. Issue 11 (26th November 2021) - Kulandaisamy, A.; Nikam, Rahul; Harini, K.; Sharma, Divya; Gromiha, M. Michael
Abstract: ProThermDB (https://web.iitm.ac.in/bioinfo2/prothermdb/index.html ) is a primary resource for protein stability, which contains experimentally determined thermodynamic data for proteins and their mutants. The most recent version of ProThermDB accumulates the data obtained from both high‐ and low‐throughput experimental biophysical methods. It includes comprehensive information at four different levels, i.e.: (i) protein sequence and structure; (ii) experimental conditions; (iii) thermodynamic parameters such as Gibbs free energy, melting temperature, enthalpy, etc.; and (iv) literature. In the following protocols, we present detailed tutorials for retrieving data using different search, display and sorting options, interpretation of search results, description of each entry‐level information category, data upload and download, cross‐links with other databases, and visualization options. This protocol consists of six pictorial exercises, which are useful for biologists/users to understand the contents and organization of data in ProThermDB. Further, potential applications of ProThermDB in protein engineering are discussed. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Retrieval of experimental thermodynamic data for wild‐type and mutants of a specific protein using a simple query Basic Protocol 2 : Retrieval of stabilizing point mutations, which are located at the interior of α‐helical regions, and obtaining data by thermal denaturation methods Basic Protocol 3 : Retrieval of destabilizing point mutations, which are in β‐sheets of exposed regions, and obtaining data by chemical denaturation methods (urea and GdnHCl) Basic Protocol 4 : Retrieval of stabilizing and destabilizing point mutations in a range of physiological conditions (pH: 6‐9 and T : 20°C‐25°C) and publication years (2010‐2020) Support Protocol : Downloading the entire data of the database for academic research purposes and submission of new data in ProThermDB